Oxygen Sensing, Hypoxia Tracing and in Vivo Imaging with Functional Metalloprobes for the Early Detection of Non-communicable Diseases - Mirabello, Vincenzo; Cortezon-Tamarit, Fernando; Pascu, Sofia I. (Frontiers in Chemistry, 2018)
'Leave the Abstract empty if your article falls under any of the following categories: Review, General Commentary, Field Grand Challenge, Opinion or Specialty Grand Challenge.'